Taxes, home equity, and household mobility - Gupta, Manish (Journal of Financial Stability, 2026)
• Home equity erosion causally reduces household mobility even without negative equity. • The Tax Reform Act 1986’s mortgage-only tax shield identifies higher mortgage demand. • Exclusive mortgage deduction inflated mortgage by $7,600, squeezing equity by 8.2%. • The equity erosion reduced homeowner mobility by 3.8%. • Renter mobility remained unchanged, validating the mortgage-specific variation.